Bridging Financial Inclusion to Water and Sanitation: Insights from Indonesia - Christian Suryadi; Faisal Madjid Alyasa; Ahmad Komarulzaman; Heriyaldi (Economics Development Analysis Journal, 2024)
Lack of access to improved drinking water and sanitation has been a major worldwide challenge, especially in Indonesia. This study investigates the impact of financial inclusion on access to improved drinking water and sanitation among households in Indonesia. Using binary probit regression analysis complemented with dominance analysis, we assess the relative importance of various factors, including financial inclusion, socio-economic status, and residence, in determining access to improved drinking water and sanitation services. Our findings highlight the critical role of urban residence in facilitating access to improved drinking water and sanitation, with urban areas demonstrating significantly higher access rates. Furthermore, participation in savings emerges as a more influential factor compared to credit participation, particularly in improving access to sanitation facilities. This suggests that while both savings and credit contribute to improved access, savings play a more pronounced role in addressing the higher upfront costs associated with sanitation infrastructure. Additionally, socio-economic factors such as household expenditure and education level are found to significantly influence access to improved water and sanitation, underscoring the importance of addressing broader socio-economic disparities. Overall, our study provides valuable insights and emphasizing the need for comprehensive strategies for policymakers to enhance essential access to clean water and sanitation.